Who knows : safeguarding your privacy in a networked world - Cavoukian, Ann.; Tapscott, Don (New York : McGraw-Hill, 1997)
In this compelling book, privacy expert Ann Cavoukian teams up with Don Tapscott, author of The Digital Economy, coauthor of Paradigm Shift, and an international authority on information technology in business, to reveal the many ways in which government and corporations systematically invade our privacy and erode the confidentiality of our personal information.
The authors examine how the breakdown of technological barriers has created the formation of a vast network of information. They show how the growth of computer usage results in the rise of personal surveillance, for purposes you may not even be aware of. Where you go, what you do, how much you spend, and (by inference) how you behave and think - such "data" are stored electronically and made accessible to strangers.
Read this book to discover how your medical records, credit reports, employment background, and consumer history are woven into detailed personal profiles that are commonly bought and sold. And learn about the essential steps you must take to protect yourself against such practices.
Keywords: Privacy, Right of; Information society; Information technology